Regulation vs symbolic policy-making: genetically modified organisms in the German States - Hartung, Ulrich; Hörisch, Felix (German politics, 2018)
Germany’s federal states can enforce stricter regulations on genetically modified organisms (GMOs) than does the national government. Empirically, the study analyses two outcomes at the state level: the symbolic accession to the GMO-free network, in which regional units mobilise against the EU’s regulatory approach, and hard GMO policies/regulations. Besides focussing on political parties and environmental interest groups, the article provides various additional theoretical explanations for the variation in outcomes. The research questions are the following: what conditions a state’s accession to the GMO-free network? What conditions a state’s adoption of GMO regulations? To assess these questions, the study employs fuzzy-set qualitative comparative analysis. One finding is that the inclusion of the Green Party in government is not a predominant condition for the adoption of regulations, but ministers affiliated with the Greens are dominant drivers of symbolic policy-making. The study reveals differing regulatory action by CDU/CSU ministers in the western and eastern states, which can be explained by the differing interests of farmers. Other findings reveal that SPD ministers regulated GMOs to much the same extent as CDU/CSU or Green ministers. Environmental interest groups were also found to have positively conditioned symbolic policy-making, having no effect, however, on the adoption of concrete regulations.